New early Permian paleopoles from Sardinia confirm intra-Pangea mobility - Bachtadse, V.; Aubele, K.; Muttoni, G.; Ronchi, A.; Kirscher, Uwe; Kent, D. (Elsevier BV, 2018)
© 2018 Elsevier B.V. We present new paleomagnetic results for the early and middle Permian (18 sites and 167 samples) from sedimentary and volcanic rocks from northern and central-southern Sardinia (Italy). Characteristic directions magnetization have been retrieved using stepwise thermal demagnetization techniques. The bedding corrected site mean directions for the northern and central-southern Sardinian basins show similar inclinations but differ significantly in declination indicating rotations of up to 55° between the two regions. No indication for inclination shallowing was observed. When corrected for the opening of the Ligurian Sea in the Cenozoic and the Bay of Biscay in the Cretaceous, the resulting paleopoles for northern Sardinia (Latitude 46.6°S, Longitude 46.7°W) and southern Sardinia (Latitude 42.8°S, Longitude 35.0°E), transferred into European coordinates are displaced from the coeval reference poles for stable Europe by ~30° clockwise and ~45° counterclockwise, respectively, with a rotation pole located close to the sampling region. Statistical parameters for the inclination-only mean for the 18 sites improve after applying the appropriate tilt corrections, suggesting that the magnetization was acquired before tectonic tilt and therefore allows to date the observed rotations to predate a mid Permian(?) folding event. These new results are in agreement with paleomagnetic data from the Sardinian dyke provinces and support earlier interpretations that the differences in general strike observed there are a secondary feature. Combining the data presented here with published data for the Corso-Sardinian block and the greater Mediterranean realm, we argue that the differential block rotations identified in Permian sediments and volcanic rocks reflect post-Variscan intra-Pangea mobility localized along a wide zone of deformation.